The use of facebook in isis recruitment-an exploratory study / Nor Hanim Ibrahim, Syaripah Ruzaini Syed Aris and Fariza Hanis Abdul Razak - Syed Aris, Nor Hanim; Syed Aris, Syaripah Ruzaini; Abdul Razak, Fariza Hanis (Centre for Media and Information Warfare Studies, 2017)
Professional use of social media by militant group is a new and emerging trend. Such phenomenon had made Malaysia's national security on the verge of uncertainty. This research specifically looks at ISIS involvements in Facebook and how they have used it to recruit new members. This research focuses on analyzing the profile of potential target and to examine the methods used by them to persuade potential target to become a new member. This research also aims to propose preventive measures to reduce ISIS recruitment in Malaysia. This research uses an in-depth expert interview that involved four participants. It is clear that everybody is vulnerable to become the target especially the youth generation. The researcher also succeed in identify the method used by recruiters which is by emotional appeal, promising a rewards, Bai'ah via online and using hashtag. An outreach programme like a forum about religion, ISIS, critical thinking and digital literacy could be used to reduce ISIS recruitment in Malaysia. Other than that, the existence law need to be tighten and the public is advised to be aware of what happen in the surrounding and give a cooperation to lodge a report if seeing something suspicious. It is suggested for other studies to conduct a research that focus on the profile of the recruiters itself to have a deeper understanding about the intention, reason or objective of joining the extremist group.